Scaling solutions to 6D gauged chiral supergravity - Tolley,AJ; Burgess,CP; de,Rham C; Hoover,D (New Journal of Physics, 2006)
We construct explicitly time-dependent exact solutions to the field equations of six-dimensional (6D) gauged chiral supergravity, compactified to 4D in the presence of up to two three-branes situated within the extra dimensions. The solutions we find are scaling solutions, and are plausibly attractors which represent the late-time evolution of a broad class of initial conditions. By matching their near-brane boundary conditions to physical brane properties, we argue that these solutions (together with the known maximally symmetric solutions and a new class of non-Lorentz-invariant static solutions, which we also present here) describe the bulk geometry between a pair of three-branes with non-trivial on-brane equations of state.